An Analysis of Code Switching Used by an English Teacher in Teaching Process - Nur Afifah; Syamsul Bahri Ys; Diana Fauzia Sari (Universitas Syiah Kuala, 2020)
This research is aimed to know the types and functions of code-switching that used by an English teacher at MAN 1 Pidie. The approach of this research was qualitative method. The data were gathered from direct and indirect observation of the English teaching process in the classroom. The writer used Jendra’s (2013) theory to analyze the types of code switching and Mattson and Burenhult’s (1999) theory to analyze the functions of code switching of the selected data. The findings of this research showed that the teacher used all three types of code switching in teaching English process which includes tag code-switching, inter-sentential code-switching and intra-sentential code-switching. Based on occurrence frequency tag code-switching was the most-used type, while inter-sentential code-switching was the least. The writer also found all three functions of code-switching those are topic switch function, affective function and repetitive function. In this research, topic switch function tend to be used more frequently among others function which makes it the highest percentage.